2014
DOI: 10.1186/s12974-014-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular hemoglobin - mediator of inflammation and cell death in the choroid plexus following preterm intraventricular hemorrhage

Abstract: BackgroundIntraventricular hemorrhage (IVH) with post-hemorrhagic ventricular dilatation (PHVD) is a major cause of neurodevelopmental impairment and mortality in preterm infants. The mechanisms leading to PHVD and brain damage remain largely unknown. The choroid plexus and the ependyma, which constitute an essential part of the blood-brain barrier (BBB), are the first structures to encounter the damaging effects of extravasated blood. The breakdown of the BBB is a critical upstream event leading to brain dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 37 publications
8
85
0
Order By: Relevance
“…This was accompanied by CP cell death, caspase activation and pronounced ultrastructural changes. Similar inductions in inflammatory mediators and cell death were obtained in vitro when CP epithelial cells were exposed to met-hemoglobin, heme or CSF from preterm babies with IVH [35]. The hemoglobin scavenger, haptoglobin, prevented the adverse effects of IVH in vivo and hemoglobin or IVH CSF in vitro [35].…”
Section: Choroid Plexus As a Site Of Injurymentioning
confidence: 77%
See 1 more Smart Citation
“…This was accompanied by CP cell death, caspase activation and pronounced ultrastructural changes. Similar inductions in inflammatory mediators and cell death were obtained in vitro when CP epithelial cells were exposed to met-hemoglobin, heme or CSF from preterm babies with IVH [35]. The hemoglobin scavenger, haptoglobin, prevented the adverse effects of IVH in vivo and hemoglobin or IVH CSF in vitro [35].…”
Section: Choroid Plexus As a Site Of Injurymentioning
confidence: 77%
“…Furthermore, Gram et al [35] found a marked inflammatory response in a rabbit preterm model of IVH at 1 and 3 days. This was accompanied by CP cell death, caspase activation and pronounced ultrastructural changes.…”
Section: Choroid Plexus As a Site Of Injurymentioning
confidence: 99%
“…It has been shown that intracerebroventricular injection of the Hb-scavenger Hp in vivo reversed or reduced cellular activation, inflammatory response, structural damage, and cell death following IVH [38] (Fig. 3).…”
Section: Scavenger Studies Of Hb-metabolites Display the Importance Omentioning
confidence: 94%
“…In a preterm rabbit pup model of IVH, it was recently shown that extracellular Hb infiltrates and is widely dispersed in large regions of the cerebral periventricular white matter, especially in areas with high extracellular plasticity [37]. Furthermore, metHb was shown to be a potent inducer of pro-inflammation, displaying a strong correlation with TNF protein levels in intraventricular CSF and increased mRNA levels for TNF, IL-1β and of HO-1 in periventricular brain tissue [10,38].…”
Section: Aetiology and Studies Of Hb-related Brain Damage In Animal Mmentioning
confidence: 99%
“…A recent finding suggests that intraventricular Hb induces cytotoxic markers in astrocytes and can cause significant cell death and inflammatory activation in the choroid plexus (Gram et al, 2013, 2014). It is known that the heme moiety released by Hb interacts with intracellular heme oxygenase (HO) proteins (such as HO-1 in macrophages and HO-2 in neurons), releasing bilirubin, carbon monoxide, and iron (Fe) cations able to participate in Fenton and Haber-Weiss reactions (Lee et al, 2010; Lok et al, 2011; Wagner et al, 2003; Wang and Dore, 2007).…”
Section: Introductionmentioning
confidence: 99%